Respuesta :
Answer : [tex] 9x^2 - 25 = (3x - 5)(3x + 5) [/tex]
(1) [tex] 9x^2 - 25 = (3x - 5)(3x - 5) [/tex]
Use FOIL method to mulitply (3x – 5)(3x – 5)
[tex] (3x - 5)(3x - 5) = 9x^2 - 30x + 25 [/tex]
(2) [tex] 9x^2 - 25 = (3x - 5)(3x + 5) [/tex]
Use FOIL method to mulitply (3x - 5)(3x + 5)
[tex] (3x - 5)(3x - 5) = 9x^2 - 15x + 15x - 25 = 9x^2 - 25 [/tex]
(3) [tex] 9x^2 - 25 = -(3x + 5)(3x + 5) [/tex]
Use FOIL method to mulitply -(3x + 5)(3x + 5)
[tex] -(3x + 5)(3x + 5) = -(9x^2 + 30x + 25) = -9x^2 -30x -25 [/tex]
(4) [tex] 9x^2 - 25 = -(3x + 5)(3x - 5) [/tex]
Use FOIL method to mulitply -(3x + 5)(3x - 5)
[tex] -(3x + 5)(3x - 5) = -(9x^2 - 25) = -9x^2 + 25 [/tex]
So equation 2 is true